Optimizing yield and quality attributes of bottle gourd (Lagenaria siceraria) through growing methods and bio-regulators in semi-arid environment - MEENA, POOJA DEVI; GARHWAL, O P; BAIRWA, L N; BAGRI, R K; MEENA, O P; SHARMA, R N; SINGH, UADAL (The Indian Journal of Agricultural Sciences, 2025)
A field experiment was conducted during 2022 and 2023 at Rajasthan Agricultural Research Institute, Durgapura, Jaipur, Rajasthan to evaluate the effects of different growing methods and bio-regulators on the yield and quality of bottle gourd (Lagenaria siceraria). The experiment involved 10 treatment combinations, featuring two growing methods namely; G1, Trailing system and G2, Traditional system and five bio-regulators of different levels, viz. B1, Control; B2, NAA @200 ppm; B3, GA3 @50 ppm; B4, Ethrel @200 ppm and B5, Salicylic acid @150 ppm. The trial was laid out in a factorial randomized block design (F-RBD) with three replications. The findings revealed that the vertical trailing system resulted in significantly improved fruit length (17.7 cm), number of fruits/vine (4.1), average fruit weight (0.78 kg), fruit yield/vine (3.19 kg), total soluble solids (3.96%), total sugar content (3.07 g/100 g), crude protein content (0.51%) and ascorbic acid content (11.7 mg/100 g). Similarly, foliar application of GA3 at 50 ppm registered greater fruit length (17.9 cm), number of fruits/vine (4.13), average fruit weight (0.77 kg), yield of fruits/vine (3.16 kg), total soluble solids (3.91%), total sugar (3.08 g/100 g), crude protein (0.52%) and ascorbic acid (11.4 mg/100g) as compared to rest of the treatments. The trailing method combined with GA3 @50 ppm application offers notable enhanced yield and quality of bottle-gourd, while the use of ethrel @200 ppm may serve as a viable alternative for growers seeking similar results.